KOORDINASI DINAS PERTANIAN DAN BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) DALAM PEMBUKAAN LAHAN TANI (BAWANG MERAH) DI KABUPATEN ENREKANG - Rahmat, Rahmat; Madani, Muhlis; Abdi, Abdi (Universitas Muhammadiyah Makassar, 2023)
The purpose of this study was to find out the work plan, meetings, communication and division of tasks at the Coordination of the Agricultural Service and the Regional Disaster Management Agency for the clearing of agricultural land (shallots) in Enrekang Regency. The research method used descriptive qualitative with a total of 3 informants including the Secretary of the Regional Disaster Management Agency of Enrekang Regency, the Secretary of the Agriculture Service and the Head of the Horticulture Division of the Enrekang Regency Agricultural Office. Collecting data used observation, interviews, and documentation. While the data analysis used data reduction, data presentation, and conclusions. The results showed that the Coordination of the Agriculture Service and the Regional Disaster Management Agency (BPBD) in Farming Land Clearing (onion) in Enrekang Regency that the work plan was prepared according to the needs of local farmers, meeting carried out at the office or at the farm location, communication was carried out in realizing the work plan that had been prepared and the division of tasks was carried out in accordance with the main tasks and work functions of each field.